A Dual Level Direct Dynamics Study for the Reaction of CF2=CHCF3 (HFC‐1225 zc) and CF2=CHCF2CF3 (HFC‐1327 cz) towards OH Radicals. Issue 17 (1st May 2019) - Gupta, Parth; Rajakumar, Balla
Abstract: Long carbon‐chain framework Hydrofluoroolefin (HFOs) systems are considered to be successful alternatives to the routine Hydrofluorocarbons (HFCs). The influence of these HFOs can be understood based on their chemical interaction(s) with the atmospheric oxidants. Therefore, to better assess the impact of HFC‐ 1225zc and HFC‐ 1327cz on the Earth's atmosphere, kinetics was investigated with atmosphere's most powerful oxidant, OH radical, in the temperature range of 200–400 K using the CCSD(T)/cc‐pVTZ//M062x/6‐31+G(d, p) level of theory. Temperature dependent hindered‐rotor corrected rate coefficients for the corresponding OH‐addition and H‐abstraction channels were determined using the dual‐level direct dynamics with the Interpolated Single Point Energy method (VTST/ISPE) in conjunction with the Small‐Curvature Tunneling (SCT) corrections. Among the two channels studied, addition channels played an essential role in determining the global reactivity of these HFOs. The global rate coefficients (in 10 −13  cm 3 molecule −1 sec −1 ) obtained at 298 K are; k(CF2 =CHCF3 +OH)=9.41 and k(CF2 =CHCF2 CF3 +OH)=9.11 respectively. COF2, CF3 CHO, CF3 COCF2 OH, CF3 CF2 CH(F)O, CF3 COOH and CF3 CF2 COOH are the major products formed via the possible O2 ‐NOx initiated product degradation mechanism for these HFOs. The atmospheric lifetimes for these molecules were found to be 31 and 14 days respectively. Radiative Efficiencies (REs), Global‐Warming Potentials (GWPs), and Photochemical Ozone Creation Potentials (POCPs) are also reported as part of this work. Abstract : Temperature dependent hindered‐rotor corrected rate coefficients for the OH‐addition and H‐abstraction channels were determined using the dual‐level direct dynamics with the Interpolated Single Point Energy method (VTST/ISPE) in conjunction with the Small‐Curvature Tunneling (SCT) corrections. Kinetics was investigated with OH radicals in the temperature range of 200–400 K using the CCSD(T)/cc‐pVTZ//M062x/6‐31+G(d, p) level of theory. The global rate coefficients (in 10 −13  cm 3 molecule −1 sec −1 ) obtained at 298 K are; k(CF2 =CHCF3 +OH)=9.41 and k(CF2 =CHCF2 CF3 +OH)=9.11 respectively.